The Effects of Mindfulness Meditation-Based Complex Exercise Program on Motor and Nonmotor Symptoms and Quality of Life in Patients with Parkinson's Disease - Hye Gyeong Son; Eun-Ok Choi (Asian Nursing Research, 2018)
Purpose: The present study was to examine the effect of a meditation-based exercise program on the motor and non-motor symptoms of Parkinson’s disease (PD). Methods: Sixty three PD patients who were recruited from a university hospital were randomly assigned to the experimental group (n = 33) and to the control group (n = 30). Participants completed an 8-week Mindfulness Meditation-based Complex Exercise Program (MMBCEP) that included 6 sessions. Before and after the intervention, the Six-Minute Walk Test (6MWT), elastic band pull, chair stand test, and 2.45-meter walk test were administered for the motor symptoms and the Korean Version of Geriatric Depression Scale, The State-Trait Anxiety Inventory (STAI), the Korean-Montreal Cognitive Assessment, Parkinson’s Disease Sleep Scale (PDSS), Activities of Daily Living (ADL), and the Quality of Life of Patients with Parkinson's Disease (PDQL) were administered for non-motor symptoms. Results: Significant improvements in the motor symptoms (i.e., muscle strength (lower and upper extremity), balance, and muscle endurance) and in the non-motor symptoms (i.e., anxiety, depression, cognitive functions, sleep disturbance, quality of life, and activities of daily living) were observed. Conclusions: MMBCEP, a complex exercise program-based on mindfulness meditation, is associated with increased motor symptoms, decreased emotional disturbances (anxiety and depression) and sleep disturbance, and improved cognitive functions, quality of life, and activities of daily living. Future research should test the effects of MMBCEP with more representative PD patients. Keywords: cognition, exercise, meditation, Parkinson disease, quality of life